Improving the Stability of Metal Halide Perovskite Quantum Dots by Encapsulation - Lv, Wenzhen; Li, Ling; Xu, Mingchuan; Hong, Junxian; Tang, Xingxing; Xu, Ligang; Wu, Yinghong; Zhu, Rui; Chen, Runfeng; Huang, Wei (Advanced materials (Weinheim), 2019)
Metal halide perovskite quantum dots (PQDs), with excellent optical properties and spectacular characteristics of direct and tunable bandgaps, strong light‐absorption coefficients, high defect tolerance, and low nonradiative recombination rates, are highly attractive for modern optoelectronic devices. However, the stability issue of PQDs remains a critical challenge of this newly emerged material despite the recent rapid progress. Here, the encapsulation strategies to improve the stability of PQDs are comprehensively reviewed. A special emphasis is put on the effects of encapsulation, ranging from the improvement of chemical stability, to the inhibition of light‐induced decomposition, to the enhancement of thermal stability. Particular attention is devoted to summarizing the encapsulation approaches, including the sol–gel method, the template method, physical blending, and microencapsulation. The selection principles of encapsulation materials, including the rigid lattice or porous structure of inorganic compounds, the low penetration rate of oxygen or water, as well as the swelling–deswelling process of polymers, are addressed systematically. Special interest is put on the applications of the encapsulated PQDs with improved stability in white light‐emitting diodes, lasers, and biological applications. Finally, the main challenges in encapsulating PQDs and further investigation directions are discussed for future research to promote the development of stable metal halide perovskite materials. Encapsulation is a highly effective strategy for improving the stability of metal halide perovskite quantum dots (PQDs), giving them promise in a wide range of modern optoelectronic applications. Recent advances in the development of encapsulated PQDs are summarized, extracting fundamental understanding on the effects, the methods, and the materials of encapsulation, with particular attention on the optoelectronic applications.